Design and Development of Marketing Media Website at UD. Pasindo Pustaka Mandiri Using Design Thinking Method - Farras Zahy Fitrian Pramudya; Raharja, Pradana Ananda (Jurnal E-Komtek (Elektro-Komputer-Teknik), 2024)
Changes in consumer behavior have become a major challenge for companies in managing marketing strategies. The readiness of infrastructure and willingness to innovate have made UD. Pasindo Pustaka Mandiri require new marketing media to reach a wider sales market and adapt to current technological developments, particularly through a website. This research aims to design and build a website for UD. Pasindo Pustaka Mandiri using the Laravel framework and the design thinking methodology. The design thinking process involves five stages: Empathize, Define, Ideate, Prototype, and Test. This method was chosen because it allows researchers to deeply understand user needs. The system development using the design thinking method resulted in a marketing website. System testing applied blackbox testing with descriptive analysis, yielding a feasibility score of 97.22%, interpreted as 'very feasible.' The System Usability Scale testing produced an average score of 74.29, falling within the Acceptability Ranges with the category 'Acceptable.' According to the grade scale, the system received a 'C' category, and in terms of adjective rating, it was rated as 'Good.' Overall, it can be concluded that the resulting website is highly feasible and acceptable to the public